Remnant cholesterol is independently asssociated with an increased risk of peripheral artery disease in type 2 diabetic patients - Song, Yi; Zhao, Ying; Bai, Xiangli; Cheng, Wenzhuo; Wang, Li; Shu, Meng; Shu, Yan; Zhang, Liyin; Jin, Si (Frontiers in Endocrinology, 2023)
Background Remnant cholesterol (RC) has been correlated with a higher risk of atherosclerosis. It has been confirmed that in the general population, an elevated RC level is related to a 5-fold higher risk of peripheral arterial disease (PAD). Diabetes is one of the strongest risk factors for PAD development. However, the association between RC and PAD in the specific population of type 2 diabetes mellitus (T2DM) has not been investigated. Herein, the correlation was investigated between RC and PAD in T2DM patients. Methods In the retrospective study, the hematological parameter data of 246 T2DM patients without PAD (T2DM - WPAD) and 270 T2DM patients with PAD (T2DM - PAD) was collected. Differences in RC levels between the two groups were compared, and the association between RC and PAD severity was examined. Multifactorial regression was used to determine whether RC was a significant contributor to the development of T2DM - PAD. The diagnostic potential of RC was tested using receiver operating characteristic (ROC) curve. Results The RC levels in T2DM - PAD individuals were considerably greater than in T2DM - WPAD individuals (P < 0.001). RC had a positive correlation with disease severity. Further, multifactorial logistic regression analyses found that elevated RC levels were a major contributor to T2DM - PAD (P < 0.001). The area under the curve (AUC) of the RC for T2DM - PAD patients was 0.727. The cut-off value of RC was 0.64 mmol/L. Conclusion The RC levels were higher in T2DM - PAD patients, and were independently linked with its severity. Diabetic patients with RC levels > 0.64 mmol/L had an elevated risk of developing PAD.